COMPARISON OF METHODS FOR CALCULATING VOLUMES OF MINERAL RAW MATERIALS DURING SURFACE EXPLOITATION - Amela Kešetović; Amar Isaković; Jasmin Ćatić (Geodetski Glasnik)
The aim of this paper is to compare two geodetic methods - GNSS and aerial photogrammetry in the context of calculating the volumes of mineral resources in open-pit mines. The advantages and weaknesses of both methods are analyzed, as well as their impact on accuracy, efficiency, and costs. The results show that the GNSS method provides high accuracy on simpler and flatter terrains but demonstrates weaknesses on more complex terrains due to the approximation of the actual surface using breakpoints obtained by the GNSS method. The aerial photogrammetry method enables fast and efficient data collection and provides a detailed 3D model, making it particularly useful in hard-to-access or hazardous areas. Additionally, it significantly saves time during data collection and reduces the demand for geodetic professionals. The paper also compares volume calculation methods, emphasizing how technological advancements allow many software solutions to treat the 3D model of the subject area as a whole rather than as segments such as profiles, prisms, etc.